?PRELIMINARY STUDIES ON THE POPULATION OF PHYTONEMATODES WITH BETLEVINE (PIPER BETLE) AND THEIR CONTROL BY INDIGENOUS NEMATIC~DE (Biological Sciences - PJSIR, 1998)
Two nematicides viz: Furadan and Tenekil-M were tested for their efficacy against phytoparasitic nematodes i.e. He- licotylenchus indicus, H. digonicus, Hoplolaimus indicus, Rotylenchus renifonnis and Longidorus siddiqui that arc attacking betlevine. After 16 weeks of the experiments the number of these nematodes was reduced in treated plots than control. Tenekil-M was found to be a good nematicide. The nematicide is indigenous and economical for betlevine industry.